The applications of IoT network to enhance farming at Al-Aziziah Palm Trees Farm in Saudi Arabia - Aljumaiah, Abdulaziz; Temowo, Olusolabomi; Marseglia, Gabriella; Sciannimanico, Giulia; Otoo, Freda Naa Ayorkor; Parihar, Ravi; Al-Ashaab, Ahmed (Elsevier, 2025)
This paper explores the use of Internet of Things (IoT) technologies to reduce high water consumption and attached operational costs in date palm farming at Al-Aziziah Palm Trees Farm in Hail, Saudi Arabia. Conventional irrigation practices often lead to inefficient water use and elevated expenses, particularly from the diesel-powered water pumps. To overcome this, an on-farm living lab was deployed using Internet of Things (IoT) network for real-time sensor monitoring, where collected data is analysed using cloud analytics to enable data-driven decision-making with enhanced water efficiency. Findings demonstrate that this IoT-based system can significantly enhance irrigation accuracy for 45% reduction in water pump usage, and consequently, a notable decrease in diesel fuel consumption. The cost model developed in this study estimates significant potential savings per year. This paper presents a replicable framework for deploying IoT technologies in large-scale date palm farms, promoting economic and environmental benefits of sustainable farming practices in Saudi Arabia and similar arid regions.
Keywords: 4606 Distributed Computing and Systems Software; 46 Information and Computing Sciences; Smart farming; IoT; Date palm; Irrigation optimisation; Saudi Arabia; Water efficiency; Soil moisture sensors; Raspberry Pi; Sustainability; Cost reduction; Digital agriculture